Analisis Kontribusi Pemungutan Pajak Hotel dan Restoran terhadap Pendapatan Asli Daerah di Dispenda Kota Makassar - Andi Arifwangsa Adiningrat; Subhan Subhan; Muhammad Nur (LP3M Universitas Muhammadiyah Makassar)
Taxes are a source of state revenue, which became one of the original income (PAD) is derived from the Local Tax, which is an important indicator that is considered as the level of independence of local government in the field of finance. Hotel taxes and taxes are two types of restaurant Regional Tax whose potential is growing along with the increasing attention to supporting components. Hotel and restaurant taxes have an important role to revenue (PAD). The purpose of this study, to know how big the contribution of hotel and restaurant tax to PAD Makassar. The approach used in this study is Mix-method. And the method of analysis used is descriptive analyze the data of tax on hotel and restaurant tax. The results showed that very lack of hotel tax and the tax contributes restaurant less contributed to revenue in 2016.